The Pathways of the Inflated Beliefs of Responsibility and their Relationship to the Side- Thinking of Prisoners Practicing for Sports - Amer Saeed Al-Khagani; Haider Jasim Nema (Institute of Medico-legal Publications Pvt Ltd, 2021)
The research included the introduction and the importance of research: The importance of identifying the paths of the inflated beliefs of responsibility and their relation to the side thinking of the sports-practicing prisoners in the Division of Positions and Altesfarat in Diwaniyah. The aim of the research is: The relationship between the paths of the inflated beliefs of responsibility and the side-thinking of sports-practicing prisoners in the Diwaniyah Positions and Altesfarat Division.The Imposition of The Search: The researcher assumes that there is a real link between the paths of the inflated beliefs of responsibility and the side-thinking of the sports-practicing prisoners in the Diwaniyah Positions and Altesfarat Division.The research methodology and procedures are also included in the field, as researchers used the descriptive approach in the survey style and comparative studiesThe research sample, which is the sports-practicing prisoners, is used to discuss the tools used in research, testing used and statistical means.The results were presented and discussed, and the results were presented in tabular form and then discussed. The research contained conclusions and recommendations, the most important conclusions being: There are statistically significant moral differences between the paths of the inflated beliefs of responsibility and the side-thinking of prisoners practicing sports activity